Tres plantas de interés corológico en Andalucía oriental. - Salazar Mendías, Carlos; Algarra Ávila, José Antonio; Cañadas Sánchez, Eva; Torres Cordero, Juan Antonio (Acta Botanica Malacitana, 2002)
Three plants of chorological interest in Eastern Andalusia Palabras clave. Vegetación halófila, Fitogeograffa, provincia Betica, distrito Guadiciano- Bastetano, España. Key words. Halophilous vegetation, Phytogeography, Baetic province, Guadiciano-Bastetano district, Spain.